Pengaruh Terapi Nutrisi Terhadap Kontrol Gula Darah Pada Pasien Diabetes Melitus Di Rsud Labuang Baji Makassar - Ambiya, Nur (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Diabetes mellitus (DM) is a chronic metabolic disease whose prevalence continues to increase globally and is one of the leading causes of morbidity and mortality. One of the main strategies in managing DM is Medical Nutrition Therapy (MNT), which plays a role in controlling blood sugar levels and preventing long-term complications. Objective: This study aims to analyze the effect of nutritional therapy on blood sugar control in patients with type 2 diabetes mellitus at Labuang Baji General Hospital in Makassar. Methods: The study was conducted on June 21, 2025, using a quasi-experimental pre-post test design without a control group. The sample consisted of 30 patients with type 2 DM selected using purposive sampling. The intervention involved providing nutritional therapy according to diabetes diet recommendations (carbohydrates 45–55%, protein 15–20%, fat 25–30%) and educating patients on the “T-plate” method for 4 weeks. Fasting blood sugar levels were measured before and after the intervention. Data were analyzed using a paired t-test with a significance level of p<0.05. Results: There was a decrease in the average fasting blood sugar level from 176 mg/dL to 142 mg/dL after the intervention. Statistical tests showed significant results with a p-value of 0.001 (p<0.05), indicating a positive effect of nutritional therapy on blood sugar control in patients. Conclusion: Nutritional therapy is effective in lowering blood sugar levels in patients with type 2 diabetes mellitus at Labuang Baji General Hospital in Makassar. It is recommended that nutritional therapy become an integral part of diabetes management in healthcare facilities and that long-term monitoring be conducted to maintain optimal results.